Philosophical counseling: a useful tool for our daily life - Frunză, Sandu (Journal for the study of religions and ideologies, 2022)
We have focused in this text on some general aspects of philosophical counseling and on the openness that the practicing philosopher has in relation to other types of counseling. We have made some clarifications that can help the reader to see a possible profile of the client requesting philosophical counseling services and we hope that he will find himself in this description. Philosophical counseling is a professional practice, based on dialogue in solving existential problems, ethical dilemmas, metaphysical crises, and lack of solutions regarding the meaning of existence. At the same time, philosophical counseling involves a search for truth and authenticity, solutions for personal development and the formulation of a philosophy of personal and professional success. In the counseling relationship you can find support in a wide variety of issues, from personal reflections on life, death, and happiness, to very intimate aspects of personal feelings. Against this background we have revealed some aspects of love, as they can be found in the counseling practices and in the daily life of those who resort to philosophical counseling.